PERANCANGAN ROBOT PENDETEKSI KEBOCORAN PIPA GAS MENGGUNAKAN ALGORITMA WALL FOLLOWER - NURRAHMAN (INFOKOM (Informatika & Komputer), 2018)
The risk that can occur from the use of a pipe as a medium to siphon PG gas isoccurring leakage of that pipe. The biggest risk of leakage is when the LPG gas leakedfrom that pipeline ignited by a spark, it will cause an explosion or fires that may damagearound facilities and cause in casualties and injuries. The Wheeled Robot leakage LPGgas detection is the form of a robot, which will move to follow the room contained LPGgas pipeline with DC motor and ultrasonic sensor.The robot is also equipped with a gas sensor to detect gas leakage in the pipe.The brain in this robot is a microconroller program using the algorithm wall follower,with the result that the robot can move and detect the gas leak automatically withouthuman help. The result is a robot will trace the existing pipe in the room with normalspeed at the time has not detected a gas leak.By the time the robot starts detecting a leak, the robot will move at full speedtowards the source of the leak. Getting closer to the source of the leak, the robot willmove but its speed begins to decrease slowly, until right at the source of the leak, then therobot will stop.